2022
DOI: 10.1186/s12889-021-12443-8
|View full text |Cite
|
Sign up to set email alerts
|

A school-based educational on-site vaccination intervention for adolescents in an urban area in Germany: feasibility and psychometric properties of instruments in a pilot study

Abstract: Background Vaccination rates for measles, mumps, and rubella (MMR) and diphtheria, tetanus, pertussis, and polio (Tdap-IPV) are not optimal among German adolescents. Education in combination with easy access to vaccination may be a promising approach to improve vaccination rates. The present paper describes a pilot study of a planned cluster randomized controlled trial (cRCT) in which we aim to improve MMR and Tdap-IPV vaccination rates together with knowledge and self-efficacy in a school sett… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…The study quality assessment is presented in Table 2. Concerning methodological quality, none of the articles included was classified as strong, five obtained moderate classification [23,25,27,29,30], and eight were poor quality [24,26,[31][32][33][34][35]. Considering the instruments categories, it was verified that: (1) only one study was classified as strong in the selection of bias parameter [23], since the rate of participants exceed the 80%, which may be representative of the target population; (2) the randomized controlled trials or controlled clinical trials were classified as strong study design (n = 5) [27,29,[33][34][35], while other type of design was classified as moderate (n = 8) [23][24][25][26]28,[30][31][32]; (3) seven studies revealed no baseline differences between groups in the confounders' section or accounted for at least 80% of significant confounders [24,25,27,29,30,33,35], whereas the studies performed with only one group were not evaluated at this point (n = 5) [23,26,28,31,32]; (4) only one study blinded the assessors and participants, being classified as strong [27]; (5...…”
Section: Study Quality and Risk Of Biasmentioning
confidence: 99%
See 4 more Smart Citations
“…The study quality assessment is presented in Table 2. Concerning methodological quality, none of the articles included was classified as strong, five obtained moderate classification [23,25,27,29,30], and eight were poor quality [24,26,[31][32][33][34][35]. Considering the instruments categories, it was verified that: (1) only one study was classified as strong in the selection of bias parameter [23], since the rate of participants exceed the 80%, which may be representative of the target population; (2) the randomized controlled trials or controlled clinical trials were classified as strong study design (n = 5) [27,29,[33][34][35], while other type of design was classified as moderate (n = 8) [23][24][25][26]28,[30][31][32]; (3) seven studies revealed no baseline differences between groups in the confounders' section or accounted for at least 80% of significant confounders [24,25,27,29,30,33,35], whereas the studies performed with only one group were not evaluated at this point (n = 5) [23,26,28,31,32]; (4) only one study blinded the assessors and participants, being classified as strong [27]; (5...…”
Section: Study Quality and Risk Of Biasmentioning
confidence: 99%
“…Concerning methodological quality, none of the articles included was classified as strong, five obtained moderate classification [23,25,27,29,30], and eight were poor quality [24,26,[31][32][33][34][35]. Considering the instruments categories, it was verified that: (1) only one study was classified as strong in the selection of bias parameter [23], since the rate of participants exceed the 80%, which may be representative of the target population; (2) the randomized controlled trials or controlled clinical trials were classified as strong study design (n = 5) [27,29,[33][34][35], while other type of design was classified as moderate (n = 8) [23][24][25][26]28,[30][31][32]; (3) seven studies revealed no baseline differences between groups in the confounders' section or accounted for at least 80% of significant confounders [24,25,27,29,30,33,35], whereas the studies performed with only one group were not evaluated at this point (n = 5) [23,26,28,31,32]; (4) only one study blinded the assessors and participants, being classified as strong [27]; (5) all studies presented valid and reliable data collection instruments; and (6) in the withdrawals and dropouts parameter, ...…”
Section: Study Quality and Risk Of Biasmentioning
confidence: 99%
See 3 more Smart Citations